2023
DOI: 10.1038/s41598-023-28626-9
|View full text |Cite
|
Sign up to set email alerts
|

A mediated moderation model of negative life events, self-esteem, rumination and parental divorce on depression among Chinese juvenile delinquents

Abstract: Little attention was paid to the prevalence of depression in Chinese juvenile delinquents who are studied in correctional work-study schools. Hence, the present study aimed to test the unique, mediating and moderating effects of negative life events, self-esteem, rumination and parental divorce on depression among Chinese juvenile delinquents. A total of 236 juvenile delinquents aged between 12 and 17 years old (M = 14.68 SD = 1.30) were recruited to accomplish a battery of self-report questionnaires concernin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…As for the other risk and protective factors included in our model, our results revealed that in accordance with previous research (Chan 2019; Khoury-Kassabri et al 2019; Mohammad and Banse 2023; Swisher and Shaw-Smith 2015; Zhang et al 2014; Zhao et al 2023), high impulsivity and arrest of a family member are associated with higher levels of juvenile delinquency. Likewise, religiosity (relationship with God), parental attachment, attachment to the neighbourhood, employment and married parents all predict lower levels of juvenile delinquency.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…As for the other risk and protective factors included in our model, our results revealed that in accordance with previous research (Chan 2019; Khoury-Kassabri et al 2019; Mohammad and Banse 2023; Swisher and Shaw-Smith 2015; Zhang et al 2014; Zhao et al 2023), high impulsivity and arrest of a family member are associated with higher levels of juvenile delinquency. Likewise, religiosity (relationship with God), parental attachment, attachment to the neighbourhood, employment and married parents all predict lower levels of juvenile delinquency.…”
Section: Discussionsupporting
confidence: 91%
“…The second set of independent variables consists of sociodemographic measures, which were also found to be correlated with juvenile delinquency (Antle et al 2020; Chan 2019; Zhao et al 2023). These include “age”, “employment” (0 = no, 1 = yes), “parental marital status” (0 = not married, 1 = married), and “family member arrest by the police” (0 = no, 1 = yes).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations